Latin American scientific contribution to ecology - Wojciechowski, Juliana; Ceschin, Fernanda; Pereto, Suelen C. A. S.; Ribas, Luiz G. S.; Bezerra, Luis A. V.; Dittrich, Jaqueline; Siqueira, Tadeu [UNESP]; Padial, Andre A. (Acad Brasileira De Ciencias, 2017)
Latin America embodies countries of special interest for ecological studies, given that areas with great value for biodiversity are located within their territories. This highlights the importance of an evaluation of ecological research in the Latin America region. We assessed the scientific participation of Latin American researchers in ecological journals, patterns of international collaboration, and defined the main characteristics of the articles. Although Latin American publications have increased in fourteen years, they accounted up to 9% of publications in Ecology. Brazil leaded the scientific production in Latin America, followed by Argentina and Mexico. In general, Latin American articles represented a low percentage of most journals total publication, with particularly low expression in high impact-factor journals. A half of the Latin American publications had international collaboration. Articles with more than five authors and with international collaboration were the most cited. Descriptive studies, mainly based in old theories, are still majority, suggesting that Ecology is in a developing stage in Latin America.
Keywords: article citations; international collaboration; journal impact factor; Neotropics; research policies; scientometrics